IMPLEMENTASI PEMBELAJARAN PENDIDIKAN PANCASILA DALAM MENUMBUHKAN SIKAP TOLERANSI DI KELAS IV SISWA SD N KEPUTRAN 1 YOGYKARTA - Yuliana, Anjar Patri; Chairiyah, Chairiyah; Nadziroh, Nadziroh; Pratomo, Wachid (STKIP Persada Khatulistiwa Sintang, 2024)
Implementation of Pancasila Education Learning in fostering an attitude of tolerance in class IV students in SD N Keputran 1 Yogyakarta. This study aims to 1) Describe the implementation of Pancasila Education Learning in fostering an attitude of tolerance in class IV students at SD N Keputran 1 Yogyakarta; 2) Knowing the supporting and inhibiting factors in the learning of Pancasila education in fostering an attitude of tolerance in class IV students in SD N Keputran 1 Yogyakarta; 3) Describe the solution of the Pancasila Education Learning Obstacles in fostering an attitude of tolerance in class IV students at SD N Keputran 1 Yogyakarta. This study uses a qualitative method. Data collection techniques using observation, interview and documentation techniques. This research instrument is guidelines for observation, interview and documentation guidelines. Data validity test using a credibility test with triangulation. Data analysis techniques using Milles and Huberman models, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of Pancasila education learning in fostering tolerance by planning learning tools, teachers motivated and provide advice and teachers reflect learning. The attitude of tolerance that has been applied is religious tolerance, cultural tolerance, social life tolerance, learning style tolerance, and preference tolerance, supporting factors in carrying out Pancasila education learning in fostering a tolerance attitude, namely the readiness of students to follow learning, positive support for school residents, religious diversity Supporting, supporting facilities and inhibiting factors, namely limited time to carry out learning, student background conditions, and lack of motivation of parents, solutions to overcome obstacles in the implementation of Pancasila education learning in fostering tolerance by providing evaluating learning materials, effective communication, providing motivation, providing Examples of tolerance behavior and improvement of learning models or approaches in the learning process.Keywords: Implementation, Learning Pancasila Education, Attitude of ToleranceÂ